The Impact of Office Environment on the Productivity of the Employees of Matarik Construction Supply: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This thesis presents the best strategy to implement a conducive working environment andensure a comfortable physical space for customers. We must also consider work performancein relation to the work environment since it is the most important element. This thesis alsoproposes a good factor about a conducive office working environment that can influence andproduce high performance and good outcomes for efficient and effective work. We mustremember that employees are more than the most important asset for any organization orcompany.The researchers have generated the following data: Table 1 shows that the highest rank is 26-33 years old. In Table 2 Gender, the highest rank is male. Table 3 Job Description: Thehighest rank is staff, which got 73.33%. Table 4 How the respondents assess the employee interms of assisting customers: the highest weighted mean is 3.27. Table 5, in terms of Reports,the highest weighted mean is 2.93. Table 6 shows that in terms of work, the highest weightedmean is 3. Table 7: Is there any significant relationship between the office environment andemployee productivity shows that the highest weighted is 3.47. Table 8 What are the problemsencountered in the office environment to the productivity of the employee in ambiance?Shows the highest weighted mean is 4.13. Table 9 Temperature: the highest weighted meanis 2.53. In Table 10, equipment, the highest weighted is 3.06.The development of the impact of the office environment on the productivity of matarikconstruction supply allows us to have an idea about the environment of construction supply. Italso helps to identify the problems, and using this information, wise decisions can be made totackle the issue appropriately. The study used a quantitative research design as best suitedfor investigation and to achieve the purpose of the study. Data were collected by distributingquestionnaires to the 15 employees at Matarik Construction Supply. The result of the studyrevealed that, to some extent, The result demonstrates the need for the employees and staffto develop and organize the office environment to have a good and conducive workenvironment.
Keywords: Organisational Management